Raman spectroscopic investigation on high refractive index glasses prepared from local quartz sand - P. Dararutana (2018)
High refractive index (RI) glasses prepared from local quartz sand and compounds of heavy elements, such as, barium carbonate, lead oxide, and bismuth oxide as major ingredients were investigated using Raman spectroscopy. The results showed changes in glass structures of different doping elements, namely, Ba, Pb, and Bi. Refractive indices, densities, and UV-vis-NIR spectra of the glass samples were also measured. The Raman spectroscopy can be used to investigate and/or identify heavy glasses, local ancient glasses as well as glass jewelry. Crown Copyright © 2008.